PENGARUH TRANSPARANSI PENGUNGKAPAN INFORMASI, KETEPATAN WAKTU PENYAJIAN LAPORAN, DAN KUALITAS AUDITOR TERHADAP REPUTASI ANNUAL REPORT PERUSAHAAN SEKTOR PUBLIK (Studi Empiris Pada Perusahaan Manufaktur Sektor Publik yang Terdaftar di Bursa Efek Indonesia) - Rhi Wadi, Claudia; Wulandari, Ika (ITB AAS Indonesia Surakarta, 2025)
This study aims to determine the effect of transparency of information disclosure, timeliness of report presentation, and auditor quality on the reputation of annual reports of public sector companies (an empirical study on manufacturing companies listed on the Indonesia Stock Exchange for 2022-2024). The population of this study is public sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. This research method uses a quantitative descriptive approach, namely by using the influence test of the application of data analysis techniques through SPSS software. The study results indicate that transparency of Information Disclosure positively affects the Reputation of Annual Reports in public sector companies listed on the Indonesia Stock Exchange for 2022-2024. Timeliness of Report Presentation positively affects the Reputation of Annual Reports in public sector companies listed on the Indonesia Stock Exchange for 2022-2024. And Auditor Quality does not affect the Reputation of Annual Reports Keywords: transparency of information disclosure, timeliness of report presentation, and auditor quality